Operational quality control and safety issues in Short-Wave Diathermy - Shields, Nora (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2003)
Short-wave Diathermy (SWD) is the therapeutic application of radiofrequency (RF) electromagnetic radiation of 27MHz by physiotherapists. The RF radiation emanating from SWD units cannot, however, be contained, but spreads out into the surrounding environment, SWD units are the primary source of occupational exposure from stray electromagnetic fields (EMFs) among physiotherapists and a number of studies have been performed to investigate the levels and the extent of this stray radiation. However, no clear information is available as to the proliferation of SWD equipment and its subsequent usage. In addition, it has not been determined what practices and policies physiotherapists adopt or should adopt to ensure their safety during the application of SWD. Furthermore, the maintenance of SWD devices has not been adequately addressed in either the physiotherapy or medical physics/ clinical engineering literature. This thesis aims to examine the availability and use of SWD in clinical practice, to develop and implement a quality control (QC) protocol for SWD units and to explore the safety practices employed by physiotherapists while applying SWD treatment.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin